1998
DOI: 10.1097/00043860-199807000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Risk Factors for Skin Breakdow With Cervical Orthotic Devices

Abstract: Aspen resulted in lower relative skin humidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Skin breakdown and pressure ulcers [32,33] due to prolonged usage have been documented in some patients particularly at the main contact points at the mandible, occiput, ears, shoulders, and clavicles. Prior studies have demonstrated that these complications may be reduced or eliminated with appropriate choice of newer, improved orthotics, an appropriate skin care regimen and monitoring, and proper fitting and application of the orthoses [34][35][36]. Prolonged or over-usage of orthotics combined with inactivity may weaken spinal muscles [8].…”
Section: Discussionmentioning
confidence: 99%
“…Skin breakdown and pressure ulcers [32,33] due to prolonged usage have been documented in some patients particularly at the main contact points at the mandible, occiput, ears, shoulders, and clavicles. Prior studies have demonstrated that these complications may be reduced or eliminated with appropriate choice of newer, improved orthotics, an appropriate skin care regimen and monitoring, and proper fitting and application of the orthoses [34][35][36]. Prolonged or over-usage of orthotics combined with inactivity may weaken spinal muscles [8].…”
Section: Discussionmentioning
confidence: 99%
“…26Y29 Three of the nine experimental studies examined the effect of C-spine immobilization devices: Stifneck, Philadelphia, Aspen, Miami-J (Ö ssur, Reykjavik, Iceland), and Newport (Aspen medical products) on TIP 30,32,33 comfort, 33 range of motion, 32 skin humidity, and skin temperature. 30 Sample sizes varied from n = 10 to n = 73. One study used a randomized block design, 25 and eight studies used crossover designs, 26Y33 of which five used randomization.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…One study used a randomized block design, 25 and eight studies used crossover designs, 26Y33 of which five used randomization. 27,29,30,32 Length of time in C-spine immobilization devices or on spinal immobilization devices varied from 5 minutes to 80 minutes and was not described in two studies. 32,33 Washout times varied from 5 minutes to 60 minutes and were not described in three studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations